Analisis Kandungan Klorofil pada Tingkat Perkembangan Daun Kopi Robusta (Coffea canephora) - ., Mawardi; Musaffa , Mahbub (JURNAL AGROPLANT, 2021)
Coffee (Coffea sp) is one of the commodities that plays an important role in the economy in Indonesia. The coffee commodity is considered promising and able to survive in the global market because coffee is a plantation product that is still very much needed by people around the world. One type of coffee that dominates people's coffee plantations in Indonesia is robusta coffee (Coffea canephora Pierre). This type of coffee is generally cultivated because it has a higher production than Arabica and Liberica coffee. Robusta coffee cultivation is inseparable from an understanding of the growth and development of these plants. Plant growth and development is strongly influenced by many factors, both factors originating from within the plant (internal) and from outside (external). The main external factors that affect plant growth and development are soil, moisture, light and water, while internal factors can include genes, hormones, anatomical structure and morphology of plant organs and chlorophyll content. Chlorophyll is one of the main factors in the growth and development of robusta coffee because it plays an important role in plant metabolism. Robusta coffee plants show color differences in the growth of their leaves. The leaves on the shoots are usually yellowish green, young leaves are light green, and old leaves are dark green. The difference in leaf color indicates differences in the content of leaf pigments, including chlorophyll pigments. This study of chlorophyll content analysis is still limited, so this research was conducted to provide scientific information about the chlorophyll content of robusta coffee leaves at different levels of leaf development. This information is initial data or comparison for research related to chlorophyll content in a plant. This research was conducted in Silo Village, Silo District, Jember Regency from April to July 2019. The experimental design used was a completely randomized design (CRD) with 3 treatments with 6 replications, the treatment consisted of yellowish green, light green, and dark green coffee leaves. The parameters observed were the content of chlorophyll a, chlorophyll b, and total chlorophyll. The results showed that the average chlorophyll content of robusta coffee leaves yellowish green was 264.73 mol/m2, light green was 361.25 mol/m2 and dark green was 508.81 mol/m2. The content of chlorophyll and robusta coffee increases with increasing leaf age (level of leaf development).